Effect Of Nano Reinforced Adhesive AL Powder And Cnt On Bending Strength Of Hybrid Laminate Structure AL - CFRP - Anhar, Muh; Laksana, Lintang Bayu Adi; Wicaksono, Dhimas; Setiawan, Fery (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
Amphibious aircraft are types of aircraft that can land on land and in water with floating components (floaters).  Amphibious aircraft are capable of landing both on land and water using float-equipped structures. In its operation, it is likely to have a bending force on the floater. When the floater is replaced with a hybrid composite, it is likely to have a light load and high beding value bending value. During operation, the floater is subjected to significant bending forces. Replacing the floater with a hybrid composite results in a lighter structure with improved bending strength. This study aims to analyze the bending test of hybrid composites reinforced with carbon fiber and aluminum faceplates. This study aims to evaluate the bending strength of hybrid composites reinforced with carbon fiber and aluminum faceplates. The method used in this study is vacuum bagging, where the sample is combined with epoxy resin and mixed with carbon nanotube (CNT) nanoparticles and aluminum powder (AL). The study was conducted with adhesive resin, surface treatment and the addition of nano particles to determine the effect of the bending strength of the composite. This study aims to analyze the effect of surface treatment and nanoparticle addition on the flexural strength of the hybrid composite.  The results showed that had a high bending value compared to the variation of specimens without surface treatment or nano particles. Specimens treated with surface modification and nanoparticles exhibited higher bending strength than those without either treatment. The highest bending stress value was obtained by the CNT variation of 133.89 MPa followed by the variation without nano particles of 98.59 MPa, then the variation without surface treatment of 91.76 MPa, and the one with the smallest value was the AL variation of 61.02 MPa. Macro photo analysis after bending test shows the presence of Mixed-mode defects in the specimen. This shows that specimens that have surface treatment and nano particles have better bonds and are able to fill the void in the empty area, so that the bending strength is good. This study provides an important contribution to understanding the variation of adhesives and nano particles on the bending strength of hybrid composites. This study offers preliminary insights into how variations in adhesives and nanoparticles influence the bending strength of a specific hybrid composite system.